Morphological features of compensatory and reparative processes of the cecum in the long term of the experiment using polycaprolactone thread modified with L-arginine - O.M. Pronina; S.M. Bilash; I.V. Ksyonz; M.M. Kobeniak; A.V. Pirog-Zakaznikova; Ya.O. Oliinichenko; M.M. Koptev; S.V. Donchenko; B.S. Kononov; V.V. Oleksiienko (Хірургія дитячого віку)
When performing surgery, the surgeon should be aware of the direct impact of the suture material on the structure of the sutured tissues and the condition of the postoperative scar, as the right surgical material is the key to rapid and successful wound healing. Therefore, searching for the safest surgical material, especially in pediatric abdominal surgery, is an urgent problem today.